Cutaneous Basal Cell Carcinoma Arising in Odontogenic Cutaneous Fistula - Kim, Nam Gyun; Kim, Jun Oh; Park, Young Ji; Kim, Jun Sik; Lee, Yoon Jung; Lee, Kyung Suk (Archives of craniofacial surgery, 2017)
An odontogenic cutaneous fistula is a pathological communication between the outer skin surface of the face and the oral cavity. Facial cutaneous fistula is a complication of odontogenic infection that is often misdiagnosed with skin infection. We report a rare case, which was diagnosed as basal cell carcinoma based on the biopsy of skin lesions in the patient who had been diagnosed with odontogenic cutaneous fistula. A 64-year-old male patient presented with a cutaneous odontogenic fistula. The patient had undergone surgical extraction of fistula tract and loose tooth before dermatology or plastic surgery consultation. With the biopsy and computed tomography, it was confirmed that fistula and basal cell carcinoma. However, the connection between the fistula and skin cancer was not clear. Positron emission tomography-computed tomography scan was performed and was not detected as other local or distant metastasis. After that, wide excision of the skin lesion was performed. Although skin cancer is not commonly observed, it is necessary to rule out this disease entity by performing biopsy of skin lesions.